Cross-modal Restoration of Juvenile-like Ocular Dominance Plasticity after Increasing GABAergic Inhibition. (21st November 2018) - Teichert, Manuel; Isstas, Marcel; Wieske, Franziska; Winter, Christine; Bolz, Jürgen
Highlights: Whisker deprivation restores "adult-like" ocular dominance plasticity in the primary visual cortex of fully adult mice. This is accompanied with reduced GABA levels in the visual cortex. However, re-increasing GABA levels with diazepam does not abolish reactivated ocular dominance plasticity. Strikingly, this treatment changes the signature of visual cortex plasticity from "adult-like" to "juvenile-like". This cross-modally restored "juvenile-like" plasticity is NMDA receptor dependent. Abstract: In juvenile and young adult mice monocular deprivation (MD) shifts the ocular dominance (OD) of binocular neurons in the primary visual cortex (V1) away from the deprived eye. However, OD plasticity is completely absent in mice older than 110 days, but can be reactivated by treatments which decrease GABA levels in V1. Typically, these OD shifts can be prevented by increasing GABAergic transmission with diazepam. We could recently demonstrate that both bilateral whisker and auditory deprivation (WD, AD), can also restore OD plasticity in mice older than 110 days, since MD for 7 days in WD mice caused a potentiation of V1 input through the ipsilateral (open) eye, the characteristic feature of OD plasticity of "young adult" mice. Here we examined whether WD for 7 days also decreases GABA levels. For this, we performed post mortem HPLC analysis of V1 tissue. Indeed, we found that WD significantly decreased GABA levels in V1. Surprisingly, enhancing GABAergic inhibition by diazepam did not abolish OD shifts in WD mice, as revealed by repeated intrinsic signal imaging. On the contrary, this treatment led to a depression of V1 input through the previously closed contralateral eye, the characteristic signature of OD plasticity in juvenile mice during the critical period. Interestingly, the same result was obtained after AD. Taken together, these results suggest that cross-modally restored OD plasticity does not only depend on reduction of GABA levels in V1, but also requires other, so far unknown mechanisms.